Social inequalities in health : new evidence and policy implications - Siegrist, Johannes; Marmot, M. G. (Oxford : Oxford University Press, 2006)
Bringing together a panel of international experts, this book aims to provide answers to the complex reasons behind social inequalities in health, explaining scientific evidence and discussing its policy implications. The topics include the role of family in early life, social integration and health, and successful ways of facing adversity.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social medicine -- Europe; Equality